An extra X does not prevent acquired hemophilia – Pregnancy-associated acquired hemophilia A. Issue 151 (March 2017) - Barg, Assaf A.; Livnat, Tami; Kenet, Gili
ABSTRACT: Acquired hemophilia A (AHA) is a severe bleeding disorder caused by autoantibodies against clotting factor VIII (FVIII). With an estimated annual incidence of 1.3 to 1.5 per million, AHA is a rare disease. An extremely rare form of AHA has been described among women in the peripartum period, and may present with peripartum hemorrhage. Notably, although hemorrhagic symptoms commonly present 1–4 months around delivery, they may occur up to 1 year after parturition. When caring for a mother with AHA it is important to note that Factor VIII inhibitor may be transferred via the placenta from the mother to the fetus. Hence the newborn may also be affected. It is important to increase the awareness of Gynecologists for clinical symptoms and laboratory signs of AHA in order to avoid delayed diagnosis. Treatment may involve use of bypass agents to control hemorrhage, despite the risk of thrombosis, while immunomodulation (with increasing role for Rituximab) may be required to eradicate the inhibiting antibodies. Our review will evaluate the epidemiology, diagnosis, clinical course and treatment of peripartum AHA, focusing upon mother and infant care.